PERAN NOTARIS PENERIMA PROTOKOL DALAM KELANJUTAN PRAKTIK KENOTARIATAN: PENGELOLAAN PROTOKOL NOTARIS YANG MENINGGAL DUNIA - viona, Viona Pratiwi Sitorus; Simamora, Janpatar (Jurnal Media Informatika, 2025)
This research examines the roles and responsibilities of recipient notaries in managing notarial protocols of deceased notaries. Notarial protocols are state archives that hold significant legal value and must be maintained even after the death of the protocol-holding notary. This study employs a normative legal research method with a library research approach. The research method focuses on analyzing library materials and legislation related to the role of recipient notaries and the procedures for transferring notarial protocols of deceased notaries. The research findings indicate that there are mechanisms regulated in the Notary Position Law regarding the procedures for transferring notarial protocols from deceased notaries to recipient notaries. This process involves active participation from heirs, the Regional Supervisory Council (MPD), and the recipient notary. The importance of the recipient notary's role is reflected in their responsibility to maintain the authenticity and security of documents within the notarial protocol, as well as to continue providing services related to these documents to members of the public who require them.